Synthesis of New Coumarin and 2-quinolone Derivatives with Expected Biological Activities - Kawkab Y. Saour; Ridha I. Al-Bayati; Mohammed K. Hadi (College of Pharmacy University of Baghdad, 2017)
A series of new coumarin and N-amino-2-quinolone derivatives have been synthesized. The reaction of coumarin (1) with excess of  Hydrazine hydrate 98% yielded 1-amino-2-quinolone (2), Compound (2) was reacted with different Sulfonyl chloride to yield Sulfonamides [ N-(2-oxoquinolin-1(2H)-yl) methane sulfonamide (3), N-(2-oxoquinolin-1(2H)-yl) Benzene sulfonamide (4) and 4-methyl-N-(2-oxoquinolin-1(2H)-yl) benzene sulfonamide (5) ], while  reaction of  2-(4-methyl-2-oxo-2H-chromen-7-yloxy) acetic acid (8) with different amines yielded compounds [  2-(4-methyl-2-oxo-2H-chromen-7-yloxy)-N-(2-oxoquinolin-1(2H)-yl) acetamide (9) and N-(5-methyl-1,3,4-thiadiazol-2-yl)-2-(4-methyl-2-oxo-2H-chromen-7-yloxy)acetamide (10) ] through amide linkage.The reactions and purity of the products were checked by TLC. The structures of the final compounds and their intermediates were confirmed by their melting points, IR spectroscopy, and elemental microanalysis.The coumarin and N-amino-2-quinolone derivatives were evaluated for their anti bacterial and antifungal activity. Key words: coumarin , 1-amino-2-quinolone, sulfonamide, amide, biological activity